On the vertical bundle of a pseudo-Finsler manifold - Aurel Bejancu; Hani Reda Farran (International Journal of Mathematics and Mathematical Sciences)
We define the Liouville distribution on the tangent bundle of a pseudo-Finsler manifold and prove that it is integrable. Also, we find geometric properties of both leaves of Liouville distribution and the vertical distribution.